Analysis Of Reduce Technical Loss Of Energy Due To Unbalanced Loading At Home Connections Using MPR Innovation (Reduce Technical Loss From House Connections) 20 kV Distribution At PT PLN (Persero) - Hartadi Constatius Duheta; Solly Aryza; Siti Anisah (INFOKUM, 2021)
PT PLN (Persero) has several ULP throughout Indonesia with a loss of 4-7%. Factors that cause shrinkage include the loss of electrical energy due to an imbalance in the use of electrical loads that are not balanced in each phase. The loss reduction program to overcome these problems, one of which uses the MPR method of load balancing (Reducing Technical Loss from House Connections) in New Installs, with more customers and increasing kWH sales growth, very important in controlling losses from balancing the transformer load. The results of the analysis of 10 samples of 20 kV Distribution Transformers in Feeders showed a decrease in transformer load imbalance >30% which previously amounted to 3 transformers to 1 transformer and a decrease or saving of 18.612 kWh at peak load.